Circular RNA expression profiling in the nucleus accumbens: Effects of electroacupuncture treatment on morphine‐induced conditioned place preference. (26th June 2019) - Zhang, Han; Wang, Qian; Wang, Qisheng; Liu, Anlong; Qin, Fenfen; Sun, Qinmei; Li, Qian; Gu, Yun; Tang, Zongxiang; Lu, Shengfeng; Lu, Zhigang
Abstract: Electroacupuncture (EA) has been developed on the basis of traditional Chinese acupuncture. EA can suppress craving in opioid addicts and opioid‐seeking responses in rodents. However, the molecular mechanism of EA on the rewarding properties of morphine and craving responses is not known. Here, we have applied a conditioned place preference paradigm in mice to measure morphine‐induced rewarding effects along with EA treatment. Circular RNAs (circRNAs) can function as micro RNA (miRNA) sponges to effectively regulate gene expression levels. CircRNA profiling within the nucleus accumbens (NAc) was performed in EA‐treated and sham‐treated mice. Following RNAseq, data were analyzed by gene ontology (GO) and Kyoto Encyclopedia Genes and Genomes (KEGG) tools. We identified 112 significantly differentially expressed circRNAs, including 51 that were up‐regulated and 61 that were down‐regulated. Our bioinformatics analyses show that these differentially expressed circRNAs map into pathways that are mainly involved with renin secretion and the cGMP‐PKG signaling. We further constructed a circRNA‐miRNA network that predicts the potential roles of the differentially expressed circRNAs and the interaction of circRNAs with miRNAs. Our secondary sequencing and bioinformatics analysis in the NAc after EA treatment on morphine‐induced CPP provides putative novel targets on molecular mechanisms involved in morphine reinforcement and possibly craving. Abstract : We have applied a conditioned place preference paradigm in mice to measure morphine‐induced rewarding effects along with EA treatment. CircRNA profiling within the nucleus accumbens was performed in EA‐treated and sham‐treated mice. The following RNAseq data were analyzed by gene ontology and Kyoto Encyclopedia Genes and Genomes tools. We identified the significantly differentially expressed circRNAs and constructed a circRNA‐miRNA network that predicts the potential roles of the differentially expressed circRNAs and the interaction of circRNAs with miRNAs.